AN ELABORATION ON THE NEW MAN ACCORDING TO EPHESIANS 4:20-24 AND THE TRIPLE PLANETARY CRISIS - Mamondole, Krets; Londo, Desilya Abigael (SoCul: International Journal of Research in Social Cultural Issues, 2024)
The study aims to comprehend the concept of the New Man according to Ephesians 4:20-24 and the Triple Planetary Crisis today in all its aspects, Christian eco-theology and its role in Christian understanding, and the implementation of the concept of the New Man for the Triple Planetary Crisis. Hence, the research was focused on environmental sustainability by integrating religious values and ethics, which could produce applicable solutions in society. In relation to this matter, exploring the meaning of the biblical text of Ephesians 4:20–24 and connect it to the reality of the planetary crisis was conducted accordingly. In addition, it also focuses on interpretation rather than numerical measurement. The result reveals that the implementation of the new man concept based on Ephesians 4:20-24, in relation to the Triple Planetary Crisis, is considered appropriate to be explained as a channel that can help humans, especially Christians, to see how beautifully God created this universe. Furthermore, it reaffirms how God's work on earth to restore and redeem humanity from sin excludes no one. Paul emphasizes in his letter that the new man must take on a new identity in Christ. This identity will be possessed by every Christian once they have shed their old selves, which are still under the bondage of sin. Therefore, the Bible serves as the foundation that enables humanity to understand God's love for this world. By knowing God and His love, humanity will be able to love everything they encounter around them. The human nature that often glorifies itself should no longer be the way of life for every person in Christ. The glory of God must be the standard for human way of life.